2019
DOI: 10.1097/01.ogx.0000604496.36351.f9
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nationwide Recommendations to Support Prenatal Counseling in Extreme Prematurity

Abstract: (Abstracted from Pediatrics 2019;143(6):e20183253) Guidelines on management of extreme prematurity differ regarding the lowest limits of gestation for which active support can or should be offered the recommendations for the role of parents in the decision making. In addition, the use of gestational age (GA) as a cutoff has been debated because other factors also determine prenatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Published guidelines also recommend, assuming there is a second parent in the family structure, that both parents should be present for the counseling. 3 We found that for more than half of the premature birth counseling sessions, the mother's primary support-person was not in attendance. This is concerning as decision-making is compromised when counseling is not provided to the whole decision-making family unit.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Published guidelines also recommend, assuming there is a second parent in the family structure, that both parents should be present for the counseling. 3 We found that for more than half of the premature birth counseling sessions, the mother's primary support-person was not in attendance. This is concerning as decision-making is compromised when counseling is not provided to the whole decision-making family unit.…”
Section: Discussionmentioning
confidence: 75%
“…2 To prepare for this role, parents meet face to face with neonatal counselors to receive prematurity information recommended by the American Academy of Pediatrics. 3 This information includes probability for survival, the difficulties surviving children face later in life, accuracy of the estimated gestational age, and factors that influence neonatal outcomes. Based on this knowledge, parents make resuscitation choices that best align with their reli-gious, cultural, and family beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Preparatory materials were shared electronically in advance of the session. Fellows were given articles on periviability counseling recommendations [ 3 , 4 ]. Faculty facilitators were given information on key learning points for each section of the didactic.…”
Section: Technical Reportmentioning
confidence: 99%
“…There is literature on recommended practices for content to include in antenatal counseling related to periviability and extreme prematurity. Prereading on this topic was assigned to the trainees to ensure they felt prepared to present relevant medical information [ 3 , 4 ]. Anecdotally, providing medical information is the area in which most physicians feel comfortable as compared with addressing emotions, so clinicians have a tendency to provide too much information as a way of staying in their comfort zone.…”
Section: Technical Reportmentioning
confidence: 99%
See 1 more Smart Citation